(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
We live in a modern society where institutions have their data systems and databases. They are used to organize the internal work of the institution with the aim to serve people and the community. Almost each of the state institutions are having its own unique way to gather and collect data and it does not always mean that it is possible to connect these data or use them by all involved partners during multidisciplinary and multisectoral cooperation. Do these data systems serve people or do people “serve” them? Are these data useful and accessible to carry out research and to make policy conclusions and have cost-benefit analysis? The author is analyzing available data from the perspective of different aims of research, including cost-benefit analysis, which is not a widely used method in Latvia, especially, in the field of criminal justice. The article is also modeling the situational analysis in the case where there is a need to carry out crime prevention activities and rehabilitation for the victim of violence and how the implementation of Barnahus model can support that. How do institutions exchange data? Can they have access to the data systems and do these technologies serve the community and children? The answer is simple – the keyword is still humanity and the human aspect is still the main to make sure that data systems and databases are serving people and not vice versa.